Communication education in Malaysia: early days to recent years - Syed Abdullah Idid, Syed Arabi (Penerbit UKM Press, 2019)
This paper provides a historical perspective on communication studies in Malaysia since its beginning in 1970. Government policies and support in addition to institutional factors shaped the development of communication education in Malaysia. History is important for scholars of communication to understand the foundations and influences that have shaped the development of the communication field. The communication programmes in public universities were American oriented in the early years but took a Malaysian orientation later. This paper traces the first juncture when media education was first introduced, in the second juncture when it was accepted as an academic subject at the tertiary level, and the final juncture as it evolved into an internationally recognised field of study. This paper made references to newspaper and annual reports of communication influences throughout the years but highlights the opinions and comments made by early educators through a series of interviews conducted between the years 2013 to 2017. The paper then discusses the growth of the communication programmes in the universities. To conclude, a discussion of future challenges in the communication field are discussed. As communication education in Malaysia progresses, universities will face increasing pressures in terms of funding, competition and loyalty to the foundations of the field.